2013
DOI: 10.1186/1471-2334-13-476
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of first-line antiretroviral therapy and correlates of longitudinal changes in CD4 and viral load among HIV-infected children in Ghana

Abstract: Background: Antiretroviral therapy (ART) scale-up in resource-limited countries, with limited capacity for CD4 and HIV viral load monitoring, presents a unique challenge. We determined the effectiveness of first-line ART in a real world pediatric HIV clinic and explored associations between readily obtainable patient data and the trajectories of change in CD4 count and HIV viral load. Methods: We performed a longitudinal study of a cohort of HIV-infected children initiating ART at the Korle-Bu Teaching Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
40
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 34 publications
6
40
2
Order By: Relevance
“…As shown by the first derivative plot, the rate of CD4 increase in response of treatment was high during the first 10 months and stabilized later. This analysis also revealed that there was no difference in the trend of CD4 counts in the long-run among patients who initiated with EFV or NVP containing regimen which is inline with previous study conducted in Ghana [18]. Considering only the NRTI backbones, there was difference in the evolution of log CD4 cell counts which is consistent with the study in Italy [45].…”
Section: Discussionsupporting
confidence: 89%
“…As shown by the first derivative plot, the rate of CD4 increase in response of treatment was high during the first 10 months and stabilized later. This analysis also revealed that there was no difference in the trend of CD4 counts in the long-run among patients who initiated with EFV or NVP containing regimen which is inline with previous study conducted in Ghana [18]. Considering only the NRTI backbones, there was difference in the evolution of log CD4 cell counts which is consistent with the study in Italy [45].…”
Section: Discussionsupporting
confidence: 89%
“…The results do however support the need for virologic monitoring as a better strategy for early detection of virologic failure especially with increased duration of ART exposure, since immunologic monitoring is a poor predictor of treatment failure. Our ndings are in agreement with previous Sub-Saharan Africa studies which have shown that clinical and immunologic monitoring is not su cient to detect virologic failure in a timely manner [32][33][34], which further supports the need for viral load testing as a strategy to monitor response to treatment in children. This is similar to ndings from a study done in Uganda and Zimbabwe, the ARROW TRIAL which highlighted the importance of con rming virological failure before switching to second-line ART, since some children with detectable low-level viraemia spontaneously resuppressed [35].…”
Section: Discussionsupporting
confidence: 91%
“…From our finding, this cutoff may be too high, thereby leading to high prevalence of virologic failure and subsequent CD4+ T-cell decline. Moreover, early virologic failure may be missed, resulting in evolution of drug resistant HIV variants in HIV-infected children in sub-Saharan Africa [37,38]. Further studies on the clinical significance of frequency of episodes of detectable viremia in HIV-infected children are needed to inform appropriate cutoffs for virologic failure.…”
Section: Discussionmentioning
confidence: 99%